Predictors of treatment failure of tubal pregnancy with single-dose methotrexate regimen – a systematic review and meta-analysis - Lili Tang; Sipei Nie; Ling Ling; Qian Zhu (Journal of Obstetrics and Gynaecology)
Background Ectopic pregnancies represent a potentially life-threatening medical emergency, with 95% being tubal. This meta-analysis aimed to identify early predictors for single-dose methotrexate (MTX) treatment failure in tubal pregnancies.Methods A literature search was conducted across several databases from their inception to December 2023, with references in the selected studies manually reviewed. 14 studies involving 2,804 patients were included in this meta-analysis.Results The results revealed that higher serum beta-human chorionic gonadotropin (β-hCG) levels on Day 1 (SMD = 1.25, 95% CI 0.73–1.77), foetal cardiac activity presence (OR = 12.64, 95% CI 3.15–50.75), adnexal mass presence (OR = 4.66, 95% CI 2.02–10.74), yolk sac presence (OR = 5.35, 95% CI 2.33–12.27), thicker endometrium (MD = 1.74, 95% CI 0.30–3.19), more number of previous ectopic pregnancies (MD = 0.21, 95% CI 0.13–0.30), history of pelvic inflammatory disease (PID) (OR = 3.97, 95% CI 2.02–7.79), higher progesterone levels on Day 1 (SMD = 0.22, 95% CI 0.07–0.36), a higher 48-hour pre-treatment increment in serum β-hCG percentage (MD = 11.46, 95% CI 2.95–19.98), and a higher percentage of serum β-hCG change from Day 4 to Day 0/1 (SMD = 2.58, 95% CI 1.02–4.14) were early predictive factors for treatment failure of tubal pregnancy with the MTX single-dose regimen.Conclusions This review clarifies early predictive factors for treatment failure with the MTX single-dose regimen in tubal pregnancies. High-risk tubal pregnancies likely to fail MTX monotherapy could be identified earlier, allowing for personalised intervention measures to be implemented at an early stage to prevent harm and improve treatment outcomes.